Islamic Religious Education Social Competence of Teachers in Increasing Students' Tolerant Attitudes: Qualitative Study in State High Schools of Jambi City - M.Rohimin; S.Sagaf; Muhammad Fadhil (International Journal of Islamic Thought and Humanities, 2024)
This research describes the efforts of Islamic religious education teachers to increase students' attitudes of tolerance and the social competence of Islamic religious education teachers as contributors to increasing students' attitudes of tolerance. The author's approach in this research is qualitative; the type of research is descriptive research analysis. The research location is State High School X, Jambi City. Data collection was carried out using observation, interviews, and documentation techniques. Determining research subjects used Snowball sampling. Data analysis techniques were carried out using data reduction, data presentation, drawing conclusions, and verifying research results' trustworthiness using extended participation techniques, careful observation, data triangulation, and supervisor consultation. The results of this research refer to the social competence of Islamic Religious Education Teachers as a factor that encourages students at State High School X Jambi City to increase their tolerance attitudes as well as the efforts made by teachers to increase students' tolerance attitudes, the need for an attitude of tolerance in various aspects, including tolerance in different opinions, or differences in religion, different ethnicities and cultures which makes it a benchmark that an attitude of tolerance is needed by every Indonesian citizen who has a variety of cultures, ethnicities and religions and as a solution in dealing with ethnic, cultural and religious differences in the school, community and state environment.